1993
DOI: 10.1017/s0022215100125150
|View full text |Cite
|
Sign up to set email alerts
|

Gastric pull-up by eversion stripping of oesophagus

Abstract: Gastric pull-up is a reliable method of one-stage reconstruction following total laryngopharyngoesophagectomy (TLPE). However, the technique of blunt finger dissection for extrapleural extraction of the oesophagus is liable to produce chest complications like pneumothorax. We report a series of 45 patients who underwent gastric pull-up using the technique of oesophageal extraction by stripping which produced virtually no thoracic complications. This simple technique has greatly reduced morbidity associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Rajan et al 20 described the use of vein stripper to extract esophagus, eversion stripping, the esophagus, at the same time excising the tumor from the larynx, pharynx, and esophagus, with a significant reduction in morbidity compared with the Akiyama et al study. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Rajan et al 20 described the use of vein stripper to extract esophagus, eversion stripping, the esophagus, at the same time excising the tumor from the larynx, pharynx, and esophagus, with a significant reduction in morbidity compared with the Akiyama et al study. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Blunt esophageal dissection without thoracotomy was first reported by Turner in 1936 for carcinoma of the thoracic esophagus, but indications for this operation are decreasing due to the widespread of endoscopic mucosal resection and the advancement of thoracoscopic surgery [4], [5], [6]. This operation is indicated as a radical surgery option for patients with superficial, mucosal cancer, or multiple early cancers of the esophagus that are difficult endoscopic or thoracoscopic resection cases.…”
Section: Discussionmentioning
confidence: 99%
“…A small comparative study involving 70 patients with stripping and transhiatal esophagectomy (Orringer's Technique) showed that stripping had a shorter operative time and lower blood loss, favoring the stripping technique. [11][12][13] At our center, we advocate minimally invasive or robotic McKeown esophagectomy as a treatment option for multifocal esophageal dysplasia that is not suitable for endoscopic resection. Total minimally invasive or hybrid esophagectomy has consistently demonstrated a lower rate of pulmonary complications compared to open esophagectomy.…”
Section: Surgical Approachmentioning
confidence: 99%
“…A small comparative study involving 70 patients with stripping and transhiatal esophagectomy (Orringer’s Technique) showed that stripping had a shorter operative time and lower blood loss, favoring the stripping technique. 11-13…”
Section: Surgical Approachmentioning
confidence: 99%